Chimeric plasmid that replicates autonomously in both Escherichia coli and Neurospora crassa. - Hughes, K (1983)
A hybrid pBR322 plasmid (designated pDV1001) containing two functional Escherichia coli antibiotic resistance genes (kanr and camr) and a qa-2+ gene from Neurospora crassa transforms N. crassa qa-2- mutants to qa-2+ with a frequency of ca. 5 X 10(-5) per regenerated spheroplast (ca. 100 transformants per microgram of plasmid DNA). This plasmid can replicate autonomously without integrating into the N. crassa genome. The autonomously replicating hybrid plasmid was detected in N. crassa transformants by Southern gel hybridizations. DNA from these transformants can be recovered by retransformation back into E. coli aroD recipients and selection for chloramphenicol resistance. These E. coli transformants complement an aroD mutant. The hybrid plasmid DNA present in the E. coli transformants remains unchanged on the basis of DNA restriction enzyme analyses. The original, nonhomokaryotic N. crassa transformants can be maintained on a selective medium, but there is as yet no evidence that the self-replicating plasmid can be transmitted through meiosis. In addition, the self-replicating plasmid often integrates into the N. crassa genome and then is inherited in a generally stable fashion through meiosis. Our findings suggest that this plasmid, or some derivative of it, will prove useful as a routine shuttle vector for cloning genes in N. crassa.